Defending Abused Women: Beginning a Critique of New Zealand Criminal Law - McDonald, E (Victoria University of Wellington Law Review, 1997)
The role of abuse in the lives of women who offend has been an issue in a number of recent high profile cases. This article considers the application of a number of defences to cases of violent female offending and concludes that the substantive law does not adequately address the abusive context in which women, as opposed to men, commit criminal acts.